Effect of preoperative predigested formula vs. polymeric formula on bowel function recovery after definitive surgery for small intestinal entero-atmospheric fistula in patients with chyme reinfusion - Tian, Weiliang; Yao, Zheng; Xu, Xin; Luo, Shikun; Zhao, Risheng (Frontiers in Nutrition, 2022)
Purpose The purpose of this study is to compare the effect of preoperative predigested formula vs. polymeric formula on bowel function recovery following definitive surgery (DS) for small intestinal enteroatmospheric fistula (EAF). Methods In this retrospective study, from January 2005 to December 2019, the patients with small intestinal EAF and receiving a DS were enrolled. During the preoperative treatment, each patient received enteral nutrition via nasojejunal feeding and chyme reinfusion. The enrolled subjects were classified into two groups, based on their formula type: polymeric formula and predigested formula. Then, propensity scores matching (PSM) was used to further divide these patients into PSM polymeric formula group or PSM predigested formula group. The clinical characteristics of the groups were analyzed. Result A total of 137 patients were finally enrolled, with 72 patients in the polymeric formula group and 65 patients in predigested formula group. The postoperative ileus was manifested in a total of 61 (44.5%) cases, with 27 (37.5%) in the polymeric formula group and 34 (52.3%) in the predigested formula group (P = 0.04). It was predicted that the polymeric formula could result in a reduction in postoperative ileus (OR = 0.47; 95% CI: 0.21–0.95; P = 0.04). After 1:1 PSM, there were 110 patients included. The postoperative ileus was observed in 47 patients, with 18 (32.7%) in the polymeric formula group and 29 (52.7%) in the predigested formula group (P = 0.03). After PSM, the polymeric formula demonstrated a reduction in the incidence of postoperative ileus (OR = 0.42; 95% CI: 0.19–0.92; P = 0.03). Conclusion Compared with predigested formula, the preoperative polymeric formula appears to be associated with earlier recovery of bowel function after DS for EAF.